1994
DOI: 10.1159/000126755
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Secretion Patterns of Corticotropin-Releasing Hormone, Arginine Vasopressin and ACTH as Shown by Intensive Sampling of Pituitary Venous Blood from Horses

Abstract: To characterize the short-term ACTH secretion pattern and to investigate factors regulating it, pituitary venous (PV) blood was collected using our nonsurgical method from 8 unperturbed horses every 20 or 30 s for approximately 1 h. In all but 1 horse, sampling occurred during the broad circadian maximum in plasma cortisol concentrations. Concentrations of corticotropin-releasing hormone (CRH; n = 7 horses), arginine vasopressin (AVP), ACTH and cortisol were measured by radioimmunoassay. In all horses, CRH, AV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Peptide isolated from equine hypothalami was equipotent with human CRF both in an in vitro bioassay and in human plasma binding protein assay [30,31]. Corticotropin-releasing factor concentrations in equine pituitary venous blood are lower compared with other species [32], and the number of peaks per hour as detected by a cluster program averaged 2.8 AE 1.2 standard error of the mean and 10.1 AE 1.9 for CRF and AVP, respectively [33]. To the authors' knowledge, CRF structure analysis has not been performed in the bovine species yet.…”
Section: Central Functionmentioning
confidence: 99%
“…Peptide isolated from equine hypothalami was equipotent with human CRF both in an in vitro bioassay and in human plasma binding protein assay [30,31]. Corticotropin-releasing factor concentrations in equine pituitary venous blood are lower compared with other species [32], and the number of peaks per hour as detected by a cluster program averaged 2.8 AE 1.2 standard error of the mean and 10.1 AE 1.9 for CRF and AVP, respectively [33]. To the authors' knowledge, CRF structure analysis has not been performed in the bovine species yet.…”
Section: Central Functionmentioning
confidence: 99%
“…The procedures to collect portal blood for analysis of CRH and VP present some technical challenges, especially in rodents, in which the use of anesthetics and problems with possible contamination of portal blood with peptides in the pituitary stalk make data on the effects of stress difficult to interpret (Antoni et al, 1990;Plotsky, 1988;Tannahill et al, 1991). Studies in sheep and horse have shown rapid and equal elevations in CRH and VP in the pituitary portal circulation following stress (Alexander et al, 1994;Alexander et al, 1997;Battaglia et al, 1998;Engler et al, 1989). The same studies in sheep show that some stressors, such as ketamine anesthesia, cause selective increases in VP (Engler et al, 1989).…”
Section: Preferential Vasopressin Expression During Chronic Stressmentioning
confidence: 99%
“…Central regulation unfolds via paraventricular nuclear release of corticotropin-releasing hormone (CRH) and AVP into hypophysial portal blood in discrete bursts (1,30). Intermittent neuronal outflow of CRH and AVP putatively constitutes the primary pulse renewal process.…”
mentioning
confidence: 99%
“…Intermittent neuronal outflow of CRH and AVP putatively constitutes the primary pulse renewal process. These secretagogues stimulate exocytotic release and de novo synthesis of ACTH by the anterior pituitary gland (1,5,9,24,25,32,40). Secreted ACTH drives the production of aldosterone and glucocorticoids by the adrenal zona glomerulosa and fasciculata (9).…”
mentioning
confidence: 99%